STUDENTS’ ATTITUDES TOWARD VIDEO-RECORDED PRESENTATIONS IN ENHANCING ENGLISH ORAL PRESENTATION SKILLS IN AN ESP SETTING - Novita, Dian; Rachmawati, Dwita Laksmita; Suseno, Edy (JR-ELT (Journal of Research in English Language Teaching), 2025)
In the English for Specific Purposes (ESP) context, where students must communicate effectively for academic and professional goals, oral presentation skills are especially important. However, many college students struggle with nervousness, low self-esteem, and a lack of opportunities to practice speaking English in traditional live presentations. The current study examines students’ opinions regarding the usage of video-recorded presentations as a substitute oral presentation task in an ESP class to address the issues. 26 students studying Civil Engineering at a private university in Indonesia participated in the study, which used a quantitative research approach. Students’ opinions prior to, during, and following video-recorded presentations were examined using a closed-ended questionnaire using a five-point Likert scale. The results show that students' perceptions of video-recorded presentations are generally favourable. Pronunciation, fluency, grammatical accuracy, and presentation structure were all evaluated by most participants as being improved by this method. Additionally, speaking anxiety was lessened, confidence was boosted, and adequate preparation time was provided by video-recorded presentations. Students' enthusiasm was also bolstered by encouraging comments from their teachers and peers. Video-recorded presentations were seen as a helpful and encouraging learning technique, even though they required extra preparation time. The study concludes that, in ESP and English as a Foreign Language (EFL) context, video-recorded presentations can be a useful teaching technique for improving students' oral presentation skills.